Frontier Governance: Contested and plural authorities in a Karen village after the ceasefire. (3rd March 2022) - KYED, HELENE MARIA
Abstract: This article applies the concept of frontier to analytically understand the forms of border governance that are developing in a former combat zone after the signing of a ceasefire agreement between the Myanmar government and the Karen National Union (KNU). In particular, it explores border governance through the lens of judicial interventions, moral ordering, and control of crime. Based on ethnographic fieldwork in 2016–2018, it shows how a Karen-populated area changed from being a military combat zone to an area that is the target of civilian state-making efforts by both the KNU and the Myanmar state. These efforts intermingle and compete, and yet each form of state-making remains incomplete and contested. This has resulted in pluralized authorities and partly overlapping forms of what I conceptualize as 'frontier border governance'. With its focus on two competing state-making actors, the article adds new insights to the burgeoning literature on frontiers, which predominantly focuses on a single expansionary state.